Revised circulation scheme north of the Denmark Strait - Våge, Kjetil; Pickart, Robert S.; Spall, Michael A.; Moore, G.W.K.; Valdimarsson, Héðinn; Torres, Daniel J; Erofeeva, Svetlana Y.; Nilsen, Jan Even Ø. (Deep Sea Research Part I: Oceanographic Research Papers, 2013)
The circulation and water mass transports north of the Denmark Strait are investigated using recently collected and historical in situ data along with an idealized numerical model and atmospheric reanalysis fields. Emphasis is placed on the pathways of dense water feeding the Denmark Strait Overflow Water plume as well as the upper-layer circulation of freshwater. It is found that the East Greenland Current (EGC) bifurcates at the northern end of the Blosseville Basin, some 450 km upstream of the Denmark Strait, advecting overflow water and surface freshwater away from the boundary. This “separated EGC” flows southward adjacent to the previously identified North Icelandic Jet, indicating that approximately 70% of the Denmark Strait Overflow Water approaches the sill along the Iceland continental slope. Roughly a quarter of the freshwater transport of the EGC is diverted offshore via the bifurcation. Two hypotheses are examined to explain the existence of the separated EGC. The atmospheric fields demonstrate that flow distortion due to the orography of Greenland imparts significant vorticity into the ocean in this region. The negative wind stress curl, together with the closed bathymetric contours of the Blosseville Basin, is conducive for spinning up an anti-cyclonic gyre whose offshore branch could represent the separated EGC. An idealized numerical simulation suggests instead that the current is primarily eddy-forced. In particular, baroclinic instability of the model EGC spawns large anti-cyclones that migrate offshore and coalesce upon reaching the Iceland continental slope, resulting in the separated EGC. Regardless of the formation mechanism, the recently obtained shipboard data and historical hydrography both indicate that the separated EGC is a permanent feature of the circulation north of the Denmark Strait. Highlights •We investigate the circulation and water mass transports north of the Denmark Strait. •We find that the East Greenland Current bifurcates some 450 km north of the strait. • Most of the ...